Tyconius' Book of Rules : An Ancient Invitation to Ecclesial Hermeneutics - Lynskey, Matthew R. (Vigiliae Christianae, Supplements, 2021)
"In Tyconius' Book of Rules Matthew R. Lynskey explores the church-centric interpretation of ancient biblical exegete Tyconius in his hermeneutical treatise Liber regularum. Influential within his Donatist tradition and the broader context of early North African Christianity, Tyconius wrote one of the earliest works on exegetical theory and praxis in Latin Christianity. By investigating five key concepts undergirding Tyconius's theology of church, Lynskey demonstrates how Tyconius' ecclesiology shaped his hermeneutical enterprise. Through careful readings and close analysis of Liber regularum, this study seeks to describe Tyconius' exegesis on its own terms, reflecting on notable historical, theological, formational, and missiological implications of his ecclesial exegesis as it concerns the ancient and contemporary church"--